Driver alcohol monitoring system for vehicle safety control with emergency contact - Devanesam SimpsoN, Emmanuel; Moorthy, Kohbalan (2021)
An intelligent alcohol detection and speed limiting system is proposed using Arduino A new approach is being described to identify drunk drivers and set limitations to functionalities of their vehicles to force drivers to completely stop whenever the blood alcohol content (BAC) level is higher than the approvable limitation which is 0 08 mg/L alcohol, that is equivalent to 180 PPM in this project.